2022
DOI: 10.3390/coatings12070944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sewage Sludge Addition on Microstructure and Mechanical Properties of Kaolin-Sewage Sludge Ceramic Bricks

Abstract: The dramatic increase in sewage sludge production requires researchers to develop and explore more commercially viable ways for alleviating current environmental and socioeconomic challenges connected with its routine management. It has been established that sewage sludge can be processed to fabricate various valuable products or as fuels for electricity generation. In this research, kaolin (calcined from coal gangue) and sewage sludge were successfully used to prepare porous ceramic bricks without any additiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…In recent years, with the acceleration of the industrialization process, the scale of sewage treatment plant (WWTPs) has gradually increased, as has the production of sludge as a by-product of WWTPs [ 1 , 2 ]. Phosphorus in sewage is the main source of excessive phosphorus discharge in water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the acceleration of the industrialization process, the scale of sewage treatment plant (WWTPs) has gradually increased, as has the production of sludge as a by-product of WWTPs [ 1 , 2 ]. Phosphorus in sewage is the main source of excessive phosphorus discharge in water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the building ceramics industry has witnessed an increase in the consumption of raw materials, such as clay, quartz, feldspar, and quartz sand, to accommodate its expanding production capacity. However, recent studies have shown that utilizing low-cost industrial solid waste as substitutes for traditional raw materials or as additives to enhance the performance of ceramic materials can effectively alleviate resource scarcity issues and further mitigate the continuously increasing production costs [2][3][4][5][6]. It is noteworthy that, because of its substantial and expanding production capacity, the building ceramics industry has significant potential to mitigate the large-scale accumulation of solid waste [7].…”
Section: Introductionmentioning
confidence: 99%